Cervical Osteoblastoma: A Rare Primary Spinal Tumor - Sedain, Gopal; Shrestha, Ram K; Sharma, Mohan R (Nepal Journal of Neuroscience, 2016)
Osteoblastoma is a rare and benign osteoid producing primary bone tumor that affects mainly the long bones. It makes 5% of spinal tumors, mostly arising within the posterior elements of the spine within the second and 3rd decades of life. We managed an 18 year old patient with osteoblastoma of C6 vertebra.Nepal Journal of Neuroscience 13:51-53, 2016